2021
DOI: 10.3389/fpubh.2021.681602
|View full text |Cite
|
Sign up to set email alerts
|

Policy Implementation Science to Advance Population Health: The Potential for Learning Health Policy Systems

Abstract: Many health policies are designed with the intention of improving health outcomes for all. Yet implementation of policies are variable across contexts, potentially limiting its impact on population health outcomes. The potential impact of a policy to advance health equity depends both on the design and its implementation, requiring ongoing evaluation and stakeholder engagement. Despite the importance of health policies in shaping public health, health care policy implementation science remains underrepresented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 20 publications
(18 reference statements)
1
29
0
Order By: Relevance
“…The recent calls from the National Institutes of Health, and the NCI in particular, provide important opportunities to provide information on innovative and provoking ideas to promote health equity and address inequities and promote a diverse biomedical workforce [ 104 , 105 ]. Emerging cross-disciplinary conversations among implementation, policy scientists, and economists showcase the added value of and the promising strategies to promote equity while advancing the science of implementation [ 49 ]. Researchers will also need to seek out opportunities to engage communities across a range of social and structural dimensions (i.e., race/ethnicity, socioeconomic status, age, disability, sexual orientation, gender identity, and geographic location (e.g., rural, urban)).…”
Section: Discussionmentioning
confidence: 99%
“…The recent calls from the National Institutes of Health, and the NCI in particular, provide important opportunities to provide information on innovative and provoking ideas to promote health equity and address inequities and promote a diverse biomedical workforce [ 104 , 105 ]. Emerging cross-disciplinary conversations among implementation, policy scientists, and economists showcase the added value of and the promising strategies to promote equity while advancing the science of implementation [ 49 ]. Researchers will also need to seek out opportunities to engage communities across a range of social and structural dimensions (i.e., race/ethnicity, socioeconomic status, age, disability, sexual orientation, gender identity, and geographic location (e.g., rural, urban)).…”
Section: Discussionmentioning
confidence: 99%
“…Learning health systems have also been recommended to improve policy implementation in the field of disease prevention 35 . Doing so in this country would further support story telling about change processes from actors and voices on the frontline.…”
Section: Figurementioning
confidence: 99%
“…In this case, actors' motivation can only emanate from the highly organized and conducive nature of the work environment which sometimes are not enough in translating the intentions of policymakers into desired policy outcomes. In health care policy implementation for instance, Oh et al, (2021) have shown that the potential impact of a policy to advance health equity does not only depend on its design and implementation, but also on continuing evaluation and stakeholders' engagement. In other words, this insinuates that the process through which a policy is implemented determines how successfully each stage can deliver effective services.…”
Section: The Rational Modelmentioning
confidence: 99%